Studi Komparatif Kurikulum Matematika di Indonesia dan Malaysia Berdasarkan Framework TIMSS - Al Ayyubi, Ibnu Imam; Mulyono, Mulyono; Dewi, Nuriana Rachmani (CARTESIUS : Jurnal Pendidikan Matematika, 2025)
This study aims to compare mathematics curricula in Indonesia and Malaysia based on the TIMSS (Trends in International Mathematics and Science Study) framework. The main focus of the study is to identify differences in content and cognitive domains reflected in the two curricula, as well as to analyze the extent to which the curricula accommodate higher-order thinking skills (HOTS). Using qualitative methods, including curriculum document analysis and interviews with teachers in Indonesia, this study found that the Malaysian curriculum is more structured and emphasizes reasoning and applying skills in real-world contexts, by the TIMSS indicators. In contrast, the Indonesian curriculum, although starting to integrate HOTS elements through the Merdeka Curriculum, still faces challenges in implementation and gaps in teacher training. These differences reflect the readiness of each country to prepare students to face global challenges through relevant mathematics learning. The results of this study provide important insights for curriculum development in Indonesia and can serve as a reference for policymakers to align the curriculum with international standards. This study provides important insights for curriculum development in Indonesia, as well as recommendations for policymakers to further align the curriculum with international standards, strengthen teacher training, and integrate applied elements in mathematics learning to achieve more optimal results in international evaluations such as TIMSS.